Percutaneous Endovascular Treatment of Stenosis of Dialysis Arteriovenous Fistulas - Jagadeesh Pasupuleti; Yugandhar Samireddypalle; Saripudi S V N P Manikanta Vijay; Guntaka Srujana; Amitha Vikrama KS (Asian Journal of Medical Radiological Research, 2020)
Background: The incidence of end stage renal disease is on the rise and most of these patients are undergoing dialysis either through tunneled/non tunneled dialysis catheters or through arteriovenous fistulas. The dialysis grafts and fistulas have limited durability of about 3 years and are more prone for thrombosis and stenosis, resulting in AVF dysfunction. As the number of access sites for dialysis is limited, percutaneous endovascular management by fistuloplasty has become the accepted first line of management to increase the lifespan of these fistulas.This article discusses a series of cases of AVF dysfunction secondary to draining vein stenosis managed by percutaneous transluminal angioplasty, their outcome and short term follow up till 3 months. The aim of the study is to review the role of percutaneous endovascular management of stenosis of dialysis fistulas, its indications, safety, efficacy and short term patency. Subjects and Methods: This was a prospective observational study done in department of Radio diagnosis, Narayana medical college, Nellore. About 20 cases were performed in our institution from December 2018 to August 2019. All these cases were done in angio suite after proper dialysis through temporary catheter. Post procedure doppler was done to evaluate the improvement in flow rate of these fistulas. Results: Seventeen cases were successful with immediate restoration of optimal flow rate during dialysis. (One case developed acute thrombosis of the fistula within 24 hours post procedure, which was successfully treated by needle directed thrombolysis with good patency at three month follow up). In two cases, there was failure of the procedure as the tight stenotic segment could not be negotiated. One case had early re-stenosis of the draining vein which required repeat session of fistuloplasty within one month with occlusion of the draining vein on three month follow up. Conclusion: Fistuloplasty is a minimally invasive percutaneous procedure with established safety and efficacy to restore the normal function of dialysis fistulae/grafts. The main aim of the procedure is to restore a diameter of the draining vein adequate for optimal flow rate during dialysis. Careful patient selection is required for increasing the success rate of the procedure. Repeat sessions of angioplasty is offered for re-stenosis to increase the lifespan of fistulas. Stent placement is usually avoided except for recurrent focal stenosis in precious fistulas.